Literature Review: Faktor-Faktor Yang Mempengaruhi Tingkat Stres Pada Remaja - Muhammad Jamalludin; Sunarti Sunarti; Fatwa Tentama (Jurnal Dunia Kesmas, 2026)
Stress is a common psychological problem among adolescents and has a significant impact on mental health, social development, and academic achievement. This study aims to identify and analyze factors influencing stress levels in adolescents based on 14 research articles with a case-control design. Literature was obtained from various databases such as Google Scholar, GARUDA, PubMed, ScienceDirect, and DOAJ using keywords related to stress and adolescents. The analysis results indicate that stress in adolescents is influenced by academic pressure, family economic conditions, social relationships, social media use, and psychological factors such as self-confidence and emotional management skills. Academic pressure was the most dominant factor found. This study also revealed that the lack of validated measurement tools was a major limitation in the analyzed studies. Therefore, a multidimensional intervention approach and further research with a more robust methodology are needed to design effective prevention strategies